Возможности контроля состояния ядерного реактора при помощи времени достижения заданного уровня числом нейтронов - Рязанов, В.В. (Проблеми безпеки атомних електростанцій і Чорнобиля, 2013)
Предлагается новый метод обнаружения нарушений нормальной работы ядерного реактора – по особенностям поведения моментов случайной величины времени достижения заданного уровня числом нейтронов в реакторе. При этом не требуется проводить какие-либо эксперименты. Не требуются также и громоздкие расчеты. Можно задаться произвольным изменением реактивности во времени и получить поведение моментов времени достижения заданного уровня, соответствующее этому изменению реактивности. Возможны и аналитические подходы к указанной задаче. Пропонується новий метод виявлення порушень нормальної роботи ядерного реактора - за особливостями поведінки моментів випадкової величини часу досягнення заданого рівня числом нейтронів у реакторі. При цьому не потрібно проводити будь-які експерименти. Не потрібні також і громіздкі розрахунки. Можна
задатися довільною зміною реактивності в часі й отримати поведінку моментів часу досягнення заданого рівня,
відповідну цій зміні реактивності. Можливі й аналітичні підходи до зазначеної задачі. A new method for detecting a malfunction in the reactor - on features of behavior of the moments of the random
variable time to achieve a given level of the number of neutrons in the reactor. Under the time to achieve a given
level of neutron numbers mean random time until it reaches a stochastic process for the total number of neutrons in the
reactor at this level. This value can be considered as a stochastic analog reactor period. At the points of dangerous
changes in reactivity, which can lead to a crash, the moments (such as mean and variance) of the random variable time
to achieve the level of the number of neutrons in the reactor have singularities. Modeling the behavior of these moments
for different processes in the reactor, we can keep track of their characteristics, thereby controlling the safety of the reactor.
The considered examples show the relationship between the possible malfunction in the reactor and the specific
behavior of the moments of the time to reach a level indicating a real possibility of the proposed method of control of
NPP safety. There is no need to conduct any experiments. Not be required and cumbersome calculations. They are as
follows the reactivity in time and get the behavior of the moments of time to achieve a given level, corresponding to the
change of reactivity. It is possible analytical approaches to this problem.